Russian colonial society in Tashkent, 1865-1923 - Sahadeo, Jeff 1967- (Indiana University Press, 2007)
This intensively researched urban study dissects Russian Imperial and early Soviet rule in Islamic Central Asia from the diverse viewpoints of tsarist functionaries, Soviet bureaucrats, Russian workers, and lower-class women as well as Muslim notables and Central Asian traders. Jeff Sahadeo's stimulating analysis reveals how political, social, cultural, and demographic shifts altered the nature of this colonial community from the tsarist conquest of 1865 to 1923, when Bolshevik authorities subjected the region to strict Soviet rule. In addition to placing the building of empire in Tashkent within a broader European context, Sahadeo's account makes an important contribution to understanding the cultural impact of empire on Russia's periphery.